The influence of psychodynamically oriented therapists' attachment representations on outcome and alliance in inpatient psychotherapy - Schauenburg, Henning; Buchheim, Anna; Beckh, Kathrin; Nolte, Tobias; Brenk-Franz, Katja; Leichsenring, Falk; Strack, Micha; Dinger, Ulrike (Psychotherapy research, 2010)
The Adult Attachment Interview (AAI) was used to study 31 psychotherapists who treated 1,381 patients in intensive multimodal inpatient psychotherapy. AAI dimensional ratings of security versus insecurity and dismissiveness versus preoccupation were used to predict alliance and outcome via multilevel regression techniques (hierarchical linear modeling). There were no main effects of therapists' attachment dimensions. However, higher attachment security of the therapist was associated with both better alliance and outcome in more severely impaired patients. Implications of the findings as well as limitations of the study are discussed.